Western Civilization / Ideas, Politics & Society - Chase Myrna; Jacob James R; Jacob Margaret C; Perry Marvin; Von Laue Theodore H (Houghton Mifflin Company)
This book focus on the history of ideas, providing the ''who?'', ''what?'', ''where?'', ''when''?, and most importantly the ''why?'' of Western civilization. Map, Chronologies, Preface, The Ancient World: Foundation of the West to A.D. 500, The Middle Ages: The Christian Centuries 500-1400, Early Modern Europe: From Renaissance to Enlightenment 1350-1789, An Age of Revolution: Liberal and National and Industrial 1789-1848, An Age of Contradiction: Progress and Breakout 1848-1914, World Wars and Totalitarianism: The West in Crisis 1914-1945, The Contemporary World: The Global Age Since 1945.